Adsorption of Pb, Cd, Zn, Cu and Hg ions on Formaldehyde and Pyridine Modified Bean Husks - GO Adediran; AC Tella; HA Mohammed (Journal of Applied Sciences and Environmental Management, 2010)
Adsorption of Pb(II), Cd(II), Zn(II), Cu(II) and Hg(II) ions on formaldehyde and Pyridine modified bean husks were determined. The adsorption capacity of formaldehyde modified bean husks (mg/g) was: Pb2+, 5.01; Cd2+, 3.63; Zn2+, 2.18; Hg2+, 1.82; Cu2+, 1.58 and that of pyridine modified bean husk was: Hg2+, 6.92; Cd2+, 3.63; Pb2+, 2.64; Zn2+, 2.48; Cu2+, 1.91. The Freundlich equation parameter 1/n for the metal ions were found to be less than unity which indicates that adsorption of metals on bean husks have increased as a result of modification. The calculated value from Freundlich adsorption parameter (KF) and Langmuir adsorption parameter (qmax) showed that the adsorption capacities of the metal ions are in order of Pb2+ > Cd2+ > Zn2+ > Hg2+ > Cu2+ for formaldehyde modified bean husks and Hg2+ > Cd2+ > Pb2+ > Zn2+ > Cu2+ for pyridine modified bean husks. The binding capacity study showed that the formaldehyde modified bean husks could be employed in the removal of Pb2+ and Zn2+ from industrial effluent especially in the battery manufacturing, paints and dyes industries. This study also indicates that the pyridine modified bean husk could remove Hg2+ better than the formaldehyde modified bean husk in the printing and minting industrial effluent.